Bridging Intention and Behavior: Insights into Coworking Space Adoption in Urban Indonesia - Cynthia Sari Dewi; Mohamad Trio Febriyantoro; Sri Wahyuning Septarina; Apriliana Putri (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the factors influencing coworking space users’ behavior through the lens of the Unified Theory of Acceptance and Use of Technology (UTAUT). It integrates four key constructs Performance Expectancy, Facilitating Conditions, Price Value, and Habit to evaluate their effects on Intention to Use and Use Behavior. Employing a quantitative approach, data were collected from 212 respondents in urban coworking spaces across the Jabodetabek area and analyzed using Structural Equation Modeling (SEM). The results reveal that Performance Expectancy, Facilitating Conditions, and Habit significantly influence both Intention to Use and actual Use Behavior, whereas Price Value does not have a significant effect on intention. Users tend to favor coworking spaces for their conducive work environments and comprehensive facilities, including high-speed Wi-Fi, meeting rooms, and ergonomic workstations. However, the relatively high cost of long-term use remains a major challenge. The findings underscore the critical roles of Facilitating Conditions and Habit as primary determinants of user behavior, offering practical insights for enhancing coworking space services. Moreover, this research contributes to the development of user-centered digital platforms that improve satisfaction and adoption rates. By addressing these behavioral factors, coworking space providers can elevate service quality, better align with user preferences, and strengthen competitiveness in an increasingly dynamic work environment.